2021
DOI: 10.1121/10.0005831
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between voice-gender difference and spatial separation in release from masking in multi-talker listening environments

Abstract: Voice-gender difference and spatial separation between talkers are important cues for speech segregation in multi-talker listening environments. The goal of this study was to investigate the interactions of these two cues to explore how they influence masking release in normal hearing listeners. Speech recognition thresholds in competing speech were measured, and masking release benefits by either voice-gender difference or spatial separation cues were calculated. Results revealed that the masking releases by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
(44 reference statements)
5
13
0
Order By: Relevance
“…With the spatially separated maskers, SRTs worsened by 3.2 dB with 2-mm inter-aural mismatch, much less than the drop of 7.5 dB for the dichotic masker presentation in Xu et al [ 10 ]. This is consistent with the observation that dichotic presentation may overestimate spatial benefits for the segregation of competing speech [ 13 17 , 19 ]. Accordingly, the 1.8 dB of spatial masking release was also much less than the 7.6 dB observed in Xu et al (2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With the spatially separated maskers, SRTs worsened by 3.2 dB with 2-mm inter-aural mismatch, much less than the drop of 7.5 dB for the dichotic masker presentation in Xu et al [ 10 ]. This is consistent with the observation that dichotic presentation may overestimate spatial benefits for the segregation of competing speech [ 13 17 , 19 ]. Accordingly, the 1.8 dB of spatial masking release was also much less than the 7.6 dB observed in Xu et al (2020).…”
Section: Discussionsupporting
confidence: 91%
“…In the case of a headphone presentation, the difference between diotic and dichotic masker presentation have been used to estimate spatial masking release [ 10 ]. However, dichotic masker presentation via headphones may overestimate spatial masking release in NH listeners compared to presentations in a sound field with symmetrically placed maskers [ 13 17 ]. Head-related transfer functions (HRTFs) may help to compensate for differences in spatial masking release between headphone and sound field presentations [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial cues are particularly useful when a speech target and speech maskers are qualitatively similar, same gender for instance, due to non-energetic factors. In such cases, SRM can be as much as 10 dB or 12 dB at the widest separations for an identification task ( Marrone et al , 2008a ; Oh et al , 2021 ). In the present study, maskers were the opposite gender of the target because the running speech materials lacked a comparable voice identifier, like a call sign in the CRM corpus, but there was still between 6.7 and 8.3 dB SRM on average with 30° separation, depending on whether a background babble was present or not.…”
Section: Discussionmentioning
confidence: 99%
“…For each stimulus condition, half of the sentences were male talkers and another half were female talkers, and subjects were tested with those different talker gender conditions in separate sessions. It is noted that previous studies reported that the target talker’s gender could affect speech recognition performance in multi-talker listening situations (e.g., Oh et al, 2021 ). In the current study, the male and female voices were used as one factor to explain this gender-specific difference in multisensory speech perception benefits.…”
Section: Methodsmentioning
confidence: 99%